The Characteristics of Nusantara Tafsir Manuscript: A Methodological Study of QS. al-Baqarah by Abdul Latif Syakur - Wahidi, Ridhoul; Rahman, Riki; Nurkholis, M. (Institut Agama Islam Negeri (IAIN) Keiri, 2024)
This article examines the characteristics of the manuscript exegesis of Surah al-Baqarah by Abdul Latif Syakur. This study reinforces Islah Gusmian's analysis that tafsirs born from the 20th century to the 1990s object of study revolved around selected surahs or certain juz. This interpretive manuscript needs to reveal its characteristics to strengthen the analysis regarding the systematic presentation, sources, methods, styles, and advantages and disadvantages to demonstrate the information in the manuscript. This research is a literature study of the manuscript tafsir of QS. al-Baqarah and is descriptive analysis. This research shows that the systematic presentation of this interpretation is consistent with the order of the verses in the letter being interpreted, even though all of al-Baqarah's letters have not been completely interpreted. The method used is the global method (ijmāli). The reference sources used are the hadiths of the Prophet Saw, the sayings of ṣaḥabat, qirā'at al-Qur'ān, and sababun nuzul. The dominant style is the lughāwī style, where descriptions of mufradāt and reviews of aspects of nahwu and ṣarf color this interpretation. This interpretation is not free from advantages and disadvantages. Theoretically, the advantage of this interpretation is that it makes it easier for readers to understand the meanings of the verses of the Qur'an. Still, behind this convenience, no more detailed analysis of the interpreted verses is a drawback. Manuscript of QS. al-Baqarah interpretation fills the gap in references, adds to the collection of manuscripts in the field of interpretation, and makes new contributions to the development of Qur'anic studies in Indonesia.